Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1088/0268-1242/30/8/085006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of InAs/GaSb superlattices for mid infrared detection: p–i–n versus residual doping

Abstract: We report on the opto-electronic characterization of an InAs/GaSb superlattice (SL) midwave infrared p-i-n photodetector structure (pin-SL) in comparison with the same structure with no intentional doping (i-SL). Both structures were grown on an n-GaSb substrate using molecular beam epitaxy. The nominally undoped structure (i-SL) presented p-i-n like behavior and showed a photovoltaic mode photoresponse due to the residual doping and native defects in this material system. For ∼77 K operation, 0.76 and 0.11 A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Especially when the bias was applied on SL-GaAs sample, the optical signal showed considerable improvement (∼5 fold at 3.7 μm) over its photovoltaic mode operation at 300 K (not shown here). Note that the temperature-dependent Hall effect measurements carried out for intrinsic SL structures (designed for MWIR region) indicated that the type of majority carriers and their concentrations are affected by the choice of the substrate: SL samples grown on GaAs exhibits p-type behavior at much wider temperature range in comparison to the SL grown on GaSb [24][25][26]. Therefore, the operating temperature plays an important role for determining the type of minority carriers that conduct the photocurrent, and thus the difference between the optical behaviors under bias might be caused by the different type and density of minority carriers in the corresponding sample.…”
Section: Resultsmentioning
confidence: 99%
“…Especially when the bias was applied on SL-GaAs sample, the optical signal showed considerable improvement (∼5 fold at 3.7 μm) over its photovoltaic mode operation at 300 K (not shown here). Note that the temperature-dependent Hall effect measurements carried out for intrinsic SL structures (designed for MWIR region) indicated that the type of majority carriers and their concentrations are affected by the choice of the substrate: SL samples grown on GaAs exhibits p-type behavior at much wider temperature range in comparison to the SL grown on GaSb [24][25][26]. Therefore, the operating temperature plays an important role for determining the type of minority carriers that conduct the photocurrent, and thus the difference between the optical behaviors under bias might be caused by the different type and density of minority carriers in the corresponding sample.…”
Section: Resultsmentioning
confidence: 99%